Nominal Lexemes Morphemes Reduplication of Mandarin - Yuxin, Shi (OKARA: Jurnal Bahasa dan Sastra, 2019)
Morphologically, functions of Chinese reduplication may place categorically within the derivational domain of lexemes. In fact, whereas derivation typically forms new lexemes and can be category changing, reduplication often conveys values typically found in the inflectional domain. By using the test of categorical word and test of lexical decomposition, this research achieves shed new light on the reduplicative processes. As a result, in the nominal domain, reduplication gives as a result plural noun. In the derivational domain, nominal lexeme in reduplication has a flexible distribution of lexical items. In this case, the types of reduplication of noun in Mandarin show the process of AA, AAB, and AABB patterns.